Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.5222/jopp.2012.119
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Features of Suicide Attempt Cases Applied To Umraniye Education and Research Hospital Pediatric Emergency Department Between 2010 and 2012

Abstract: Sonuç: İntihar girişimlerinin kız cinsiyette daha sık ve en fazla oral yoldan ilaç alımı ile olduğu saptanmıştır. Alınan ilaçlar içinde en sık analjezikler ve santral sinir sistemi ilaçları (antidepresanlarantipsikotikler) görülmekteydi. Çalışmamızda, psikopatoloji oranlarının düşük olmasına rağmen intihar girişimi varlığı; ergenlerin ebeveyn ilişkileri başta olmak üzere yaşadıkları çeşitli zorlanmalar karşısında intihar girişimine yöneldiklerini düşündürmüştür.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…In the study conducted by Toklucu et al, NSAIDs and psychotropic drugs took the first place. Data compatible with the literature were obtained in terms of drug classes taken during self-poisoning [14].…”
Section: Officialsupporting
confidence: 56%
“…In the study conducted by Toklucu et al, NSAIDs and psychotropic drugs took the first place. Data compatible with the literature were obtained in terms of drug classes taken during self-poisoning [14].…”
Section: Officialsupporting
confidence: 56%
“…In Turkey, they generally focused on suicide (16,17). There is little in the scientific literature describing the characteristics of children and adolescents who present to EDs of mental health hospitals with mental health concerns.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of sex, many studies have shown that those forensic cases were more common in boys than in girls (1,4-6,10). However, it has been reported that the rates of suicide attempts increase during adolescence, and most of these cases are drug-induced poisoning cases (12,14,15); therefore, forensic events are more common in female cases (16,17). We showed that female patients were more frequently admitted than male patients among the forensic pediatric cases.…”
Section: Discussionmentioning
confidence: 55%